Kajian Bibliometrik Produktivitas Publikasi Ilmiah Dosen Unri Pada Jurnal Terindeks Scopus Berdasarkan Dalil Lotka’s Law - Thamrin Hasan; Yurnalis (Perpustakaan Universitas Riau, 2022)
Lecturers are professional educators and scientists with the main task of transforming, developing and disseminating science, technology and art through education, research and community service. The purpose of the research is to inform the pattern of productivity of Unri lecturers which are published in Scopus indexed journals, then a suitability test of the frequency distribution of Lotka's law is carried out with the frequency distribution of article authors. The method used is descriptive method with bibliometric analysis. The sample is 1128 lecturers. Data collection techniques in the form of documentation. The data analysis technique uses the following steps: determining the estimated values of Lotka's law parameters, making tables of observation frequencies and Lotka's law theoretical frequencies, and testing Lotka's law using the Kolmogorov-Smirnov (K-S). The results showed that: 1) The productivity of scientific publications for Unri lecturers indexed by Scopus was obtained as many as 3748 articles. 2) The most scientific publications of UNRI lecturers indexed by Scopus are produced by Prof. Dr. Erman Taer, S.Si., M.Sc., namely 110 articles, while the highest level of popularity based on citations is Prof. Edy Saputra, ST., MT., PhD. 3) The number of scientific publications by single works is 277 articles (7.39%), while collaborative works are 3471 articles (92.61%). 4) The total contribution of 1 article is 0.3395 or 33.95% 5) The Kolmogorov-Smirnov test at the significance level α = 0.05 obtains a value of 0.2006. The conclusions of the research show that the pattern of productivity of scientific publications of Unri lecturers does not conform to the Lotka law. The number of lecturers who contributed 1 article was 33.95% while based on Lotka it was 60%.